DNA demethylation facilitates the specific transcription of the mouse X-linked Tsga8 gene in round spermatids†. Issue 4 (12th December 2018) - Lu, Yongjie; Liao, Shunyao; Tu, Wenling; Yang, Bo; Liu, Shasha; Pei, Xue; Tao, Dachang; Lu, Yilu; Ma, Yongxin; Yang, Yuan; Liu, Yunqiang
Abstract: Some X-linked genes necessary for spermiogenesis are specifically activated in the postmeiotic germ cells. However, the regulatory mechanism about this activation is not clearly understood. Here, we examined the potential mechanism controlling the transcriptional activation of the mouse testis specific gene A8 ( Tsga8 ) gene in round spermatids. We observed that the Tsga8 expression was negatively correlated with the methylation level of the CpG sites in its core promoter. During spermatogenesis, the Tsga8 promoter was methylated in spermatogonia, and then demethylated in spermatocytes. The demethylation status of Tsga8 promoter was maintained through the postmeiotic germ cells, providing a potentially active chromatin for Tsga8 transcription. In vitro investigation showed that the E12 and Spz1 transcription factors can enhance the Tsga8 promoter activity by binding to the unmethylated E-box motif within the Tsga8 promoter. Additionally, the core Tsga8 promoter drove green fluorescent protein (GFP) expression in the germ cells of Tsga8-GFP transgenic mice, and the GFP expression pattern was similar to that of endogenous Tsga8 . Moreover, the DNA methylation profile of the Tsga8 -promoter-driven transgene was consistent with that of the endogenous Tsga8 promoter, indicating the existence of a similar epigenetic modification for the Tsga8 promoter to ensure its spatiotemporal expression in vivo. Taken together, this study reports the details of a regulatory mechanism that includes DNA methylation and transcription factors to mediate the postmeiotic expression of an X-linked gene. Abstract : DNA demethylation is the primary epigenetic modification for the Tsga8 gene expression. Spz1 may enhance the Tsga8 transcription in round spermatids.